Studi Literatur: Pengaruh Professionalisme Auditor dan Whistleblower terhadap Pengungkapan Kecurangan - Nur Hidayati; Tri Ratnawati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the influence of the professionalism of auditors and whistleblowers on disclosure of fraud. This research uses the literature study method, while data collection uses the documentation method by reviewing several journals, books, documents and other data sources that are relevant to this research. The results of this research are based on a literature review of several previous research journals showing that the professionalism of auditors and whistleblowers has a significant positive influence on disclosure of fraud.